Retinal Redetachment after Silicone Oil Removal - Jahangir, Kashif (Pakistan Journal of Ophthalmology, 2018)
Purpose: This study was conducted on 50 patients who underwent pars plana Vitrectomy with silicone oil tamponade (1000 CS) for retinal detachment. The objective of this study was to analyze and evaluate in terms of retinal redetachment, surgical technique, visual acuity, and intraocular pressure after silicone oil removal. Material and Methods: A total of 50 patients who underwent 3-port parsplana vitrectomy with Silicone oil was used as an internal tamponade were enrolled in this study. The study was conducted from March 2005 to April 2006, with a follow up period of six months after silicone oil removal. Silicone oil of 1000 centistokes viscosity had been used in these patients. Forty seven patients completed their six-month follow up. All the patients were selected by a convenience type of non-probability purposive sampling. Results: Out of a total of 47 eyes, 14 (29.8%) developed retinal re-detachment, which was within the first 3 months of silicone oil removal. The IOP of the patients decreased significantly with a mean decrease of 4mmHg after silicone oil removal. Out of 33 patients with attached retina after silicone oil removal 12 had improvement in Snellen visual acuity of two lines or more where as 21 had no improvement in their vision. We observed that the duration of silicone oil as an endotemponade had no significant affect on the rate of retinal redetachment after its removal. Conclusion: Retinal redetachment is a common finding after silicone oil removal, which, in our study more than half of re-detachment occurred in the first month of oil removal. A mean of 4mmHg drop in the intraocular pressure was observed in our study after silicone oil removal. The visual acuity improved